Assessment of Health Buildings in Hilla City According to The International ‎Standard LEEDV4‎ - Al-Anbari , Prof. Dr. Mohammad Ali; Ubaid, Alaa Hadi; Chabuk, Mahmood (International Journal of Basic and Applied Sciences, 2025)
The sustainability and functional performance of healthcare facilities are paramount for patient well-being and environmental stewardship. This study presents a pioneering assessment of five major public hospitals in Hilla City, Iraq, against the Leadership in Energy and Environmental Design (LEED) v4 for Building Design and Construction (BD+C) framework. Data was collected through comprehensive on-site audits, document analysis, and direct observation. The results reveal a significant performance disparity: the newly constructed Imam Al-Sadiq Teaching Hospital achieved a Gold rating with a score of 67 out of 110 points, demonstrating strong performance in Water Efficiency and Indoor Environmental Quality. In stark contrast, the four older hospitals (Babylon Teaching, Al-Hilla Teaching, Al Noor Children's, and Marjan Medical City) all scored below the 40-point threshold, rendering them Uncertified. This failure is primarily attributed to aging infrastructure, defunct energy systems, and a lack of sustainable operational policies. The study diagnoses these critical dysfunctions and underscores the urgent need for systematic rehabilitation. We conclude by recommending the enactment of municipal legislation requiring that all new hospital constructions and major renovations in the region adhere to LEED v4 standards to ensure a higher, more sustainable quality of healthcare infrastructure for the future.[1]
Keywords: Health Buildings, Green Rating Systems, LEED Certification, LEEDV4, sustainability